Liquid phase preparation method of nano-scale ultrafine copper powder
Through the liquid phase preparation method, combined with the technical means of adding reducing agents in segments and using dispersants and post-treatment reagents, the problem of uneven particle size distribution of nano-scale ultrafine copper powder is solved, and the preparation of high-quality nano-copper powder is realized, which is suitable for microelectronic component technology.
Patent Information
- Application Number
- CN202510008773.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-03
AI Technical Summary
In the preparation of nano-scale ultrafine copper powder, the existing technology has problems such as uneven particle size distribution, high energy consumption, low yield, difficulty in solid-liquid separation, difficult product purity and particle size distribution, and difficult to control the market demand for high-quality nano-copper powder.
The liquid phase preparation method is adopted, by configuring copper salt alcohol solution, pH adjustment aqueous solution and reducing agent solution, controlling the temperature and stirring speed, adding dispersant and post-treatment reagent, and adding reducing agent in segments to control the nucleation and growth process of copper powder, and optimizing particle size distribution.
Effective control of the particle size distribution of nano-scale ultrafine copper powder is achieved, and nano-scale ultrafine copper powder with good dispersion, narrow particle size distribution range and good roundness is obtained, which is suitable for use in the technical field of microelectronic components.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano materials, and in particular relates to a liquid phase preparation method of nano-level ultrafine copper powder. Background Art
[0002] Nano-scale ultrafine copper powder has shown broad application prospects in the fields of electronics, catalysis, biomedicine and materials science due to its unique physical and chemical properties. With the advancement of science and technology and the rapid development of emerging industries, especially the rapid advancement of 5G communications, the Internet of Things, new energy vehicles and high-performance electronic devices, the demand for nano-scale ultrafine copper powder is growing. However, traditional copper powder preparation methods, such as physical pulverization and gas phase methods, often have problems such as uneven particle size distribution, high energy consumption and low yield, which makes it difficult to meet the market demand for high-quality nano copper powder.
[0003] As an emerging and efficient preparation technology, the liquid phase method has gradually become the mainstream method for preparing nano-scale ultrafine copper powder due to its advantages such as simple equipment, short process flow and easy industrialization. The liquid phase method mainly includes γ-ray irradiation method, microemulsion method, electrochemical method and liquid phase reduction method. Among them, although the γ-ray irradiation method is easy to operate, the metal powder obtained is mostly discrete colloids, and the particle size control is difficult; the microemulsion method forms a tiny reaction space (microreactor), and under the action of surfactants, the metal molecules undergo nucleation, growth and agglomeration processes to prepare nano copper particles with small and uniform particle size, but this method requires high control of reaction conditions. The electrochemical method precipitates copper powder in a divalent copper salt solution by controlling conditions such as current density and cell voltage, which is one of the commonly used methods in industry. However, the copper powder obtained by the ordinary electrolysis method has a large particle size, uneven particle size distribution, and is mostly dendritic. In addition, the electrochemical method has high energy consumption and complex equipment.
[0004] The liquid phase reduction method is to use a reducing agent in a metal cation solution and control the reaction conditions to precipitate metal ions into metal elements at the micron or even nanometer level. This method has the advantages of mild reaction conditions, easy control, simple equipment, etc., and is suitable for large-scale industrial production. Although the liquid phase reduction method has shown great potential in the preparation of nano-level ultrafine copper powder, there are still some problems, such as difficulty in solid-liquid separation, product purity and particle size distribution. Especially in the field of microelectronic component technology, such as integrated circuits, transistors, sensors, and internal electrodes of multilayer ceramic capacitors (MLCC), the requirements for nano copper powder are higher. Not only does it require the metal crystal shape to be spherical or nearly spherical, reducing the contact area and relative force between particles, thereby reducing the wear and fatigue life decay of the material surface, and improving the dispersibility, fluidity and conductivity, the particle size also needs to be controlled at the nanometer level, preferably below 800nm, and should be evenly distributed with a narrow distribution range, so as to further improve the conductivity and improve the performance stability of microelectronic components. At the same time, anti-oxidation treatment of the surface of nano copper powder can also prevent it from being oxidized in application and reduce the life of the device.
[0005] Therefore, developing a nano-scale ultrafine copper powder with good dispersion, narrow particle size distribution range and good roundness has important scientific significance and practical application value. Summary of the invention
[0006] The purpose of the present invention is to provide a liquid phase preparation method of nano-scale ultrafine copper powder, which can not only control the distribution of D50 at different levels from 150nm to 800nm, but also optimize the particle size distribution to obtain nano-scale ultrafine copper powder with good dispersion, narrow particle size distribution range and good roundness.
[0007] A liquid phase preparation method for nano-scale ultrafine copper powder comprises the following steps:
[0008] S1. Prepare reagents and weigh drugs: prepare copper salt alcohol solution, pH adjustment aqueous solution, reducing agent solution, weigh dispersant and post-treatment reagents for standby use;
[0009] S2, preparation of copper powder: take copper salt alcohol solution in a water bath, control the temperature to room temperature, maintain stirring at a speed of 500-700r / min, add pH adjusting aqueous solution to adjust the pH of the system to 8-10, and stir for 25-35min; heat the water bath to 50-60°C, add reducing agent solution and dispersant, stir for 1-4h, let the solution stand at room temperature and remove the supernatant, wash with deionized water and anhydrous ethanol 2-3 times in turn to obtain wet copper powder;
[0010] S3, post-treatment: add alcohol solvent to the wet copper powder obtained in step S2 for dispersion, add post-treatment reagent, stir at 400-600 r / min for 50-70 min at 40-50° C., let stand and remove the supernatant, wash with deionized water and anhydrous ethanol 2-3 times in sequence, and then dry to obtain nano-scale ultrafine copper powder.
[0011] Preferably, the copper salt alcohol solution comprises copper salt and ethanol; the concentration of copper salt in the copper salt alcohol solution is 1-3 mol / L.
[0012] Preferably, the copper salt includes one or more of copper carbonate, copper sulfate, copper acetate and copper chloride.
[0013] Preferably, the pH adjusting aqueous solution comprises a pH adjusting agent.
[0014] Preferably, the pH adjuster includes one or more of sodium hydroxide, ammonia, acetic acid and sodium bicarbonate.
[0015] Preferably, when the pH adjuster is ammonia, the mass concentration of ammonia in the pH adjusting aqueous solution is 10%.
[0016] Selecting ammonia as a pH regulator and adjusting the system pH to 8-10 not only helps to obtain nano copper powder with a smaller particle size and uniform distribution, but also helps to improve the circularity of the nano copper powder and its dispersibility in the system. This may be because ammonia can form stable copper ammonia complex ions with copper ions, which not only helps to reduce the concentration of free copper ions in the solution, but also promotes the uniform reduction of copper ions during the reduction process, thereby obtaining nano copper powder with a smaller particle size and uniform distribution. At the same time, the complexation of ammonia can also improve the dispersibility of nano copper powder in the solvent, so that it forms a system with good dispersibility. In addition, the addition of ammonia may also have a positive effect on the morphology of nano copper powder, helping to form particles with regular shape and high circularity. More importantly, while adjusting the pH value, ammonia can also balance the rate of the reduction reaction to a certain extent, making the reaction more stable. Therefore, compared with alkaline substances such as sodium hydroxide or sodium bicarbonate, ammonia water has better performance as a pH regulator in the preparation of nano copper powder. Alkaline substances such as sodium hydroxide or sodium bicarbonate may cause uneven reduction rate of copper ions during the reduction process, thereby affecting the particle size distribution of nano copper powder.
[0017] Preferably, the reducing agent aqueous solution includes a reducing agent.
[0018] Preferably, the reducing agent includes one or more of glucose, ascorbic acid, hydrazine hydrate, methyl borohydride and formaldehyde; further preferably, it is ascorbic acid or hydrazine hydrate.
[0019] Ascorbic acid is selected as a reducing agent, not only because its weak reducing property makes the reaction rate of reducing copper ions relatively slow and controllable, so that it can achieve fine control in the nucleation and growth stages of copper powder, which helps to generate micro-nano copper powder with more uniform particle size and morphology; but also, ascorbic acid has the characteristics of an antioxidant, and can be directly adsorbed on the surface of copper particles through van der Waals forces during the reaction, providing effective oxidation protection for copper particles. This may be because ascorbic acid has a certain complexing effect on copper ions, which can reduce the concentration of free copper ions in the solution, thereby enhancing the control over the reduction rate. At the same time, its antioxidant properties can also ensure that the copper particles are not over-oxidized during the preparation process, ensuring the quality of the final product.
[0020] Preferably, the dispersant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, Tween 40, Tween 80 and modified pyrrolidone.
[0021] In some preferred embodiments, the dispersant may be any one of sodium dodecyl sulfate and modified pyrrolidone, or a mixture of Tween 80, sodium dodecyl sulfate and modified pyrrolidone.
[0022] Preferably, the mass ratio of Tween 80, sodium dodecyl sulfate and modified pyrrolidone is 1:(0.8-1.2):(1-2); more preferably, it is 2:2:3.
[0023] Preferably, the hydroxyl value of the Tween 80 is 65-82 mgKOH / g, the saponification value is 43-55 mgKOH / g, and the HLB value is 15.
[0024] In some preferred embodiments, the Tween 80 is purchased from Nantong Xinbaoyuan Chemical Co., Ltd.
[0025] The preparation method of the modified pyrrolidone comprises the following steps: mixing acrylic acid, sodium methyl allyl sulfonate, N-vinyl pyrrolidone and azobisisobutyronitrile, vacuum sealing and placing in an oil bath at 80-90°C for reaction for 6-12 hours, collecting the residue after the reaction, extracting the residue with dichloromethane for 48-72 hours, and placing the collected reactants in a vacuum drying oven to dry to constant weight to obtain the modified pyrrolidone.
[0026] Preferably, the molar ratio of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone is (1-3):1:(2-4); more preferably, it is 2:1:3.
[0027] Preferably, the added amount of the azobisisobutyronitrile is 0.5%-0.8% of the total mass of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone.
[0028] Acrylic acid, sodium methallyl sulfonate and N-vinyl pyrrolidone are selected as raw materials to synthesize modified pyrrolidone, and the modified pyrrolidone is used to prepare nano copper powder, which can greatly improve the dispersion effect and stability of nano copper powder. This may be because acrylic acid, as a common polymerization monomer, provides a carboxyl functional group, which increases the hydrophilicity and dispersibility of the polymer, and sodium methallyl sulfonate generates electrostatic interaction or hydrogen bonding with the surface of nano copper powder through its sodium sulfonate group, which enhances the adsorption capacity of the polymer on nano copper powder, and the pyrrolidone ring of N-vinyl pyrrolidone can form a coordination bond or π-π conjugation with the surface of nano copper powder, further improving the coating effect and dispersion stability of the polymer on nano copper powder. Through copolymerization reaction, the three form a modified pyrrolidone polymer with a special structure, which not only has excellent dispersion performance, but also can effectively improve the stability and processing performance of nano copper powder.
[0029] Preferably, the added amount of the dispersant is 0.2%-0.6% of the mass of the copper salt.
[0030] The use of Tween 80, SDS and modified pyrrolidone as dispersants can not only further avoid the agglomeration of the generated nano copper powder, thereby obtaining nano-level copper powder, but also improve the uniformity of particle size distribution and reduce the gap between large and small particles. This may be due to the synergistic effect of the three dispersants. Tween 80 and SDS effectively prevent the agglomeration of nano copper powder through electrostatic repulsion and steric hindrance, thereby helping to obtain a smaller and uniform particle size distribution. At the same time, the chemical adsorption and physical coating of modified pyrrolidone form a protective film on the surface of copper powder particles, further preventing the growth and agglomeration of particles, and helping to accurately control the particle size of copper powder. The combined effect of these dispersants not only makes the particle size distribution of nano copper powder more uniform, but also significantly improves its dispersibility in the solvent, so that the copper powder can be more evenly dispersed in the solvent to form a stable dispersion system. In addition, the synergistic effect of the three dispersants also promotes the regularization of the shape of copper powder particles, improves the circularity, and expands the application range of the prepared nano-level ultrafine copper powder.
[0031] Preferably, the post-treatment reagent includes one or more of 2,6-di-tert-butyl-4-methylphenol, sodium laurate, sodium stearate, sodium oleate and dimethylglyoxime; further preferably, sodium oleate and / or sodium stearate.
[0032] Preferably, the mass ratio of sodium oleate to sodium stearate is 1:(0.8-1.2); further preferably, it is 1:1.
[0033] Preferably, the amount of the post-treatment agent added is 40-60 times the mass of the dispersant.
[0034] Coating copper powder with a specific post-treatment reagent can achieve a good anti-oxidation effect and prevent the oxidation of nano copper powder at room temperature. This may be because, on the one hand, both sodium oleate and sodium stearate can form a dense protective film on the surface of nano copper powder. Sodium oleate has good emulsification and penetration power, and can penetrate into the tiny gaps on the surface of copper powder to form a uniform coverage; while sodium stearate can form a stable protective film on the surface of copper powder, which can effectively isolate air and moisture, thereby slowing down or preventing the oxidation process of copper powder. The film-forming ability of these two reagents is complementary, making the anti-oxidation effect more prominent. On the other hand, the functional groups in sodium oleate and sodium stearate can chemically bond with the surface of copper powder. The carboxyl and other functional groups of sodium oleate can react with the oxides or exposed copper atoms on the surface of copper powder to form chemical bonds; the hydroxyl and carboxylic acid groups of sodium stearate can also form hydrogen bonds and chemical bonds with the copper surface, thereby firmly adsorbing on the surface of copper powder. This chemical combination not only enhances the binding force between the anti-oxidation film and copper powder, but also makes the anti-oxidation film more stable and not easy to fall off. In addition, the synergistic effect between sodium oleate and sodium stearate further enhances the anti-oxidation effect. The two are complementary in chemical structure and properties. Their combined use can give full play to their respective advantages and form a denser and more uniform anti-oxidation film. At the same time, both reagents are organic reagents, which are easy to remove during use and will not cause adverse effects on subsequent applications. They are better than metal plating.
[0035] Preferably, the alcohol solvent includes one or more of methanol and ethanol; further preferably, methanol.
[0036] Preferably, in step S2, the molar ratio of the copper salt to the reducing agent is 1:(1-1.2).
[0037] In some preferred schemes, after adding the reducing agent solution and the dispersant in step S2 and stirring for 25-35 minutes, the second reducing agent solution can be added, and after reacting for another 1-5 hours, the solution is allowed to stand at room temperature and the supernatant is removed, and the wet copper powder is obtained after washing with deionized water and anhydrous ethanol for 2-3 times.
[0038] Preferably, the second reducing agent solution is consistent with the reducing agent solution.
[0039] Preferably, the amount of the second reducing agent solution added is 3-8 times the volume of the reducing agent solution in step S2.
[0040] More preferably, the second reducing agent solution can be added once, twice, three times or more. When added twice, the volume ratio of the two additions is 1: (3-5), and the stirring time for each addition is 1-2 hours. When added three times, the volume ratio of the three additions is 1: (3-5): (3-5), and the stirring time for each addition is 1-2 hours.
[0041] In the process of preparing nano copper powder, a multi-stage reduction reaction technology is adopted. By adding the second reducing agent again when the reduction of one stage is not complete, the nucleation and growth of Cu powder grains can be finely controlled. The segmented addition of reducing agent can promote the reduction of Cu ions in stages, thereby regulating the number of crystal nuclei formed and the growth rate. Especially when the amount of the second reducing agent added is 3-8 times the previous amount, it can significantly accelerate the reduction process and promote more Cu ions to be converted into copper powder particles, thereby effectively refining the particle size and making it more evenly distributed. Compared with the secondary small amount addition and the single addition, the particle size refinement effect can be further improved and the production efficiency can be improved. By controlling the amount and time of the reducing agent, the number of crystal nuclei and the growth rate can be accurately controlled, thereby achieving the directional refinement of the copper powder particle size, and controlling the distribution of D50 at different levels from 150nm to 800nm. In actual experiments, the volume of reducing solution added in the latter time is more conducive to the directional refinement of the copper powder particle size than the previous time, and nano copper powders of different particle sizes can be prepared according to different usage scenarios, while maintaining the particle size distribution and circularity of the nano copper powder.
[0042] The second aspect of the present invention provides a product prepared by the liquid phase preparation method of nano-scale ultrafine copper powder.
[0043] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0044] 1. The present invention provides a liquid phase preparation method for nano-scale ultrafine copper powder. When preparing ultrafine copper powder in liquid phase, the nucleation growth process of copper powder is controlled by adding a reducing agent in stages, and a certain amount of dispersant is added in the reduction process to ensure good dispersion of copper powder particles in the liquid phase, so as to avoid agglomeration of copper powder during liquid phase nucleation, thereby reducing the number of copper powder nuclei and increasing the particle size. Moreover, copper powder of larger size is continuously dissolved and precipitated through each stage of reduction, so as to further optimize the particle size distribution, and finally obtain nano-scale ultrafine copper powder with good dispersion, narrow particle size distribution range and good roundness, which is very suitable for application in the field of microelectronic component technology.
[0045] 2. The present invention controls the preparation process parameters to prepare ultrafine copper powder with a wide particle size distribution and good roundness and dispersibility in one stage of reduction.
[0046] 3. The present invention controls the types of copper salt and reducing agent, so that the nano copper powder prepared has good roundness and dispersion, and the copper powder particle size distribution is concentrated, the process is stable, and the performance is good.
[0047] 4. In the present invention, the reducing agent is added again when the first stage reduction reaction is not complete, and the nucleation and growth process of the Cu powder grains are further controlled through multi-stage reduction reactions, and the directional refinement of the copper powder particle size is achieved according to process control, and the D50 is controlled to be distributed in different levels from 150nm to 800nm.
[0048] 5. The present invention selects ammonia water as the pH regulator and adjusts the system pH to 8-10, which not only helps to obtain nano copper powder with smaller particle size and uniform distribution, but also helps to improve the roundness of the nano copper powder and the dispersibility in the system.
[0049] 6. The present invention uses Tween 80, SDS and modified pyrrolidone as dispersants, which can not only avoid the agglomeration of the generated nano copper powder, thereby obtaining nano-grade copper powder, but also improve the uniformity of particle size distribution and reduce the gap between large particles and small particles.
[0050] 7. In order to prevent the nano copper powder from being oxidized at room temperature, the present invention performs an anti-oxidation post-treatment on the nano copper powder. The copper powder is coated with a specific post-treatment reagent to achieve a good anti-oxidation effect. The post-treatment reagents are all organic reagents, which are easy to remove and use in applications, and are better than metal plating. DETAILED DESCRIPTION
[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] The raw materials used in the present invention are all commercially available, specifically:
[0053] Tween 80 has a hydroxyl value of 65-82 mgKOH / g, a saponification value of 43-55 mgKOH / g, and an HLB value of 15, and was purchased from Nantong Xinbaoyuan Chemical Co., Ltd.
[0054] Example 1
[0055] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0056] S1. Prepare 2 mol / L copper carbonate alcohol solution, 10% mass concentration ammonia solution, 4 mol / L ascorbic acid solution, weigh 0.2 g dispersant and 10 g post-treatment reagent.
[0057] S2, take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25°C, keep the stirring rod speed at 600r / min and stir at a constant speed, add 10% ammonia solution to adjust the pH to 9, and stir for 30min; after the solution is heated to 50°C, add 250mL of 4mol / L ascorbic acid aqueous solution to a beaker, and add 0.2g of dispersant, react for 2h, let the solution stand at room temperature and remove the supernatant, wash it with deionized water and anhydrous ethanol 3 times in turn to obtain about 64g of wet copper powder;
[0058] S3. Add 500 mL of methanol to the wet copper powder obtained after the reaction for dispersion, and add 10 g of a post-treatment reagent. Stir at 40°C and 500 r / min for 1 hour, let it stand and remove the supernatant. Wash it with deionized water and anhydrous ethanol three times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0059] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0060] The dispersant is a mixture of Tween 80, sodium dodecyl sulfate and modified pyrrolidone, with a mass ratio of 2:2:3.
[0061] The preparation method of the modified pyrrolidone comprises the following steps: mixing acrylic acid, sodium methyl allyl sulfonate, N-vinyl pyrrolidone and azobisisobutyronitrile, vacuum sealing and placing in an oil bath at 85°C for reaction for 10 hours, collecting the residue after the reaction is completed, extracting the residue with dichloromethane for 60 hours, and placing the collected reactants in a vacuum drying oven to dry to constant weight to obtain the modified pyrrolidone.
[0062] The molar ratio of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone is 2:1:3.
[0063] The added amount of azobisisobutyronitrile is 0.7% of the total mass of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone.
[0064] The post-treatment reagents are sodium oleate and sodium stearate, with a mass ratio of 1:1.
[0065] Example 2
[0066] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0067] S1. Prepare 2 mol / L copper carbonate alcohol solution, 10% ammonia solution, 4 mol / L ascorbic acid solution, weigh 0.2 g dispersant, and 10 g post-treatment reagent.
[0068] S2, take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25 ° C, and keep the stirring rod speed at 600r / min constant speed stirring, add 10% ammonia solution to adjust the pH to 9, and stir for 30min; After the solution is warmed up to 50 ° C, add 250mL of 4mol / L ascorbic acid aqueous solution in a beaker, and add 0.2g dispersant, react for 30min, continue to add 1L of 4mol / L ascorbic acid solution, react again for 2h, let the solution stand at room temperature and remove the supernatant, and wash it 3 times with deionized water and anhydrous ethanol to obtain about 64g wet copper powder;
[0069] S3. Add 500 mL of methanol to the wet copper powder obtained after the reaction for dispersion, and add 10 g of a post-treatment reagent. Stir at 40°C and 500 r / min for 1 hour, let it stand and remove the supernatant. Wash it with deionized water and anhydrous ethanol three times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0070] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0071] The dispersant is a mixture of Tween 80, sodium dodecyl sulfate and modified pyrrolidone, with a mass ratio of 2:2:3.
[0072] The preparation method of the modified pyrrolidone comprises the following steps: mixing acrylic acid, sodium methyl allyl sulfonate, N-vinyl pyrrolidone and azobisisobutyronitrile, vacuum sealing and placing in an oil bath at 85°C for reaction for 10 hours, collecting the residue after the reaction is completed, extracting the residue with dichloromethane for 60 hours, and placing the collected reactants in a vacuum drying oven to dry to constant weight to obtain the modified pyrrolidone.
[0073] The molar ratio of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone is 2:1:3.
[0074] The added amount of azobisisobutyronitrile is 0.7% of the total mass of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone.
[0075] The post-treatment reagents are sodium oleate and sodium stearate, with a mass ratio of 1:1.
[0076] Example 3
[0077] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0078] S1. Prepare 2 mol / L copper carbonate alcohol solution, 10% ammonia solution, 4 mol / L ascorbic acid solution, weigh 0.2 g dispersant, and 10 g post-treatment reagent.
[0079] S2, take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25°C, keep the stirring rod speed at 600r / min and stir at a constant speed, add 10% ammonia solution to adjust the pH to 9, and stir for 30min; after the solution is warmed to 50°C, add 250mL of 4mol / L ascorbic acid aqueous solution in a beaker, add 0.2g of dispersant, react for 30min, continue to add 200mL of 4mol / L ascorbic acid solution and react for 1h, then add 800mL of 4mol / L ascorbic acid solution, react for 1h, let the solution stand at room temperature and remove the supernatant, wash with deionized water and anhydrous ethanol 3 times to obtain about 64g wet copper powder;
[0080] S3. Add 500 mL of methanol to the wet copper powder obtained after the reaction for dispersion, and add 10 g of a post-treatment reagent. Stir at 40°C and 500 r / min for 1 hour, let it stand and remove the supernatant. Wash it with deionized water and anhydrous ethanol three times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0081] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0082] The dispersant is a mixture of Tween 80, sodium dodecyl sulfate and modified pyrrolidone, with a mass ratio of 2:2:3.
[0083] The preparation method of the modified pyrrolidone comprises the following steps: mixing acrylic acid, sodium methyl allyl sulfonate, N-vinyl pyrrolidone and azobisisobutyronitrile, vacuum sealing and placing in an oil bath at 85°C for reaction for 10 hours, collecting the residue after the reaction is completed, extracting the residue with dichloromethane for 60 hours, and placing the collected reactants in a vacuum drying oven to dry to constant weight to obtain the modified pyrrolidone.
[0084] The molar ratio of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone is 2:1:3.
[0085] The added amount of azobisisobutyronitrile is 0.7% of the total mass of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone.
[0086] The post-treatment reagents are sodium oleate and sodium stearate, with a mass ratio of 1:1.
[0087] Example 4
[0088] The difference between this embodiment and embodiment 1 is that the dispersant is polyvinyl pyrrolidone.
[0089] The K value of the polyvinyl pyrrolidone is 13.5-16.5, the molecular weight is 5000-6000, and the viscosity of the polyvinyl pyrrolidone aqueous solution with a polyvinyl pyrrolidone mass concentration of 5% at room temperature is 0.9-1.2 mPa·s. It was purchased from Gongbik New Materials Technology (Shanghai) Co., Ltd., PVPK15.
[0090] The post-treatment reagent is sodium oleate.
[0091] Example 5
[0092] The difference between this embodiment and embodiment 2 is that the dispersant is polyvinyl pyrrolidone.
[0093] The K value of the polyvinyl pyrrolidone is 13.5-16.5, the molecular weight is 5000-6000, and the viscosity of the polyvinyl pyrrolidone aqueous solution with a polyvinyl pyrrolidone mass concentration of 5% at room temperature is 0.9-1.2 mPa·s. It was purchased from Gongbik New Materials Technology (Shanghai) Co., Ltd., PVPK15.
[0094] The post-treatment reagent is sodium oleate.
[0095] Example 6
[0096] The difference between this embodiment and embodiment 3 is that the dispersant is polyvinyl pyrrolidone.
[0097] The K value of the polyvinyl pyrrolidone is 13.5-16.5, the molecular weight is 5000-6000, and the viscosity of the polyvinyl pyrrolidone aqueous solution with a polyvinyl pyrrolidone mass concentration of 5% at room temperature is 0.9-1.2 mPa·s. It was purchased from Gongbik New Materials Technology (Shanghai) Co., Ltd., PVPK15.
[0098] The post-treatment reagent is sodium oleate.
[0099] Example 7
[0100] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0101] S1. Prepare 2 mol / L copper carbonate alcohol solution, 4 mol / L sodium hydroxide solution, 80% hydrazine hydrate solution, weigh 0.2 g dispersant, and 10 g post-treatment reagent.
[0102] S2, take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25°C, keep the stirring rod speed at 600r / min and stir at a constant speed, add 4mol / L sodium hydroxide solution to adjust the pH to 9, and stir for 30min; after the solution is heated to 60°C, add 64g of 80% hydrazine hydrate solution to a beaker, and add 0.2g of dispersant, react for 1h, let the solution stand at room temperature and remove the supernatant, wash it with deionized water and anhydrous ethanol 3 times in turn to obtain about 64g of wet copper powder;
[0103] S3. Add 500 mL of methanol to the wet copper powder obtained after the reaction to disperse it, and add 10 g of post-treatment reagent. After stirring at 50°C and 500 r / min for 1 hour, let it stand and remove the supernatant. Wash it with deionized water and anhydrous ethanol three times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0104] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0105] The dispersant is sodium lauryl sulfate.
[0106] The post-treatment reagent is sodium stearate.
[0107] Example 8
[0108] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0109] S1. Prepare 2 mol / L copper carbonate alcohol solution, 4 mol / L sodium hydroxide solution, 80% hydrazine hydrate solution, weigh 0.2 g dispersant, and 10 g post-treatment reagent.
[0110] S2, take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25°C, keep the stirring rod speed at 600r / min and stir at a constant speed, add 4mol / L sodium hydroxide solution to adjust the pH to 9, and stir for 30min; after the solution is heated to 60°C, add 64g of 80% hydrazine hydrate solution to a beaker, add 0.2g of dispersant, and react for 30min; continue to add 256g of 80% hydrazine hydrate, react for 1h, let the solution stand at room temperature and remove the supernatant, wash it with deionized water and anhydrous ethanol 3 times in turn to obtain about 64g of wet copper powder;
[0111] S3. Add 500 mL of methanol to the wet copper powder obtained after the reaction to disperse it, and add 10 g of post-treatment reagent. After stirring at 50°C and 500 r / min for 1 hour, let it stand and remove the supernatant. Wash it with deionized water and anhydrous ethanol three times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0112] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0113] The dispersant is sodium lauryl sulfate.
[0114] The post-treatment reagent is sodium stearate.
[0115] Example 9
[0116] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0117] S1. Prepare 2 mol / L copper carbonate alcohol solution, 4 mol / L sodium hydroxide solution, 80% hydrazine hydrate solution, weigh 0.2 g dispersant, and 10 g post-treatment reagent.
[0118] S2, take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25°C, keep the stirring rod speed at 600r / min and stir at a constant speed, add 4mol / L sodium hydroxide solution to adjust the pH to 9, and stir for 30min; after the solution is warmed to 60°C, add 64g of 80% hydrazine hydrate solution to a beaker, add 0.2g of dispersant, and react for 30min; continue to add 128g of 80% hydrazine hydrate to react for 30min, then add 128g of 80% hydrazine hydrate, after reacting for 30min, let the solution stand at room temperature and remove the supernatant, wash it 3 times with deionized water and anhydrous ethanol in turn to obtain about 64g of wet copper powder;
[0119] S3. Add 500 mL of methanol to the wet copper powder obtained after the reaction to disperse it, and add 10 g of post-treatment reagent. After stirring at 50°C and 500 r / min for 1 hour, let it stand and remove the supernatant. Wash it with deionized water and anhydrous ethanol three times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0120] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0121] The dispersant is sodium lauryl sulfate.
[0122] The post-treatment reagent is sodium stearate.
[0123] Example 10
[0124] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0125] S1. Prepare 2 mol / L copper carbonate alcohol solution, 10% ammonia solution, 4 mol / L ascorbic acid solution, weigh 0.2 g dispersant, and 10 g post-treatment reagent.
[0126] S2, take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25 ° C, and keep the stirring rod speed at 600r / min constant speed stirring, add 10% ammonia solution to adjust the pH to 9, and stir for 30min; After the solution is warmed up to 50 ° C, add 250mL of 4mol / L ascorbic acid aqueous solution in a beaker, and add 0.2g dispersant, react for 30min and continue to add 200mL of 4mol / L ascorbic acid solution, react again for 2h and let the solution stand at room temperature and remove the supernatant, wash with deionized water and anhydrous ethanol 3 times to obtain about 64g wet copper powder;
[0127] S3. Add 500 mL of methanol to the wet copper powder obtained after the reaction for dispersion, and add 10 g of a post-treatment reagent. Stir at 40°C and 500 r / min for 1 hour, let it stand and remove the supernatant. Wash it with deionized water and anhydrous ethanol three times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0128] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0129] The dispersant is a mixture of Tween 80, sodium dodecyl sulfate and modified pyrrolidone, with a mass ratio of 2:2:3.
[0130] The preparation method of the modified pyrrolidone comprises the following steps: mixing acrylic acid, sodium methyl allyl sulfonate, N-vinyl pyrrolidone and azobisisobutyronitrile, vacuum sealing and placing in an oil bath at 85°C for reaction for 10 hours, collecting the residue after the reaction is completed, extracting the residue with dichloromethane for 60 hours, and placing the collected reactants in a vacuum drying oven to dry to constant weight to obtain the modified pyrrolidone.
[0131] The molar ratio of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone is 2:1:3.
[0132] The added amount of azobisisobutyronitrile is 0.7% of the total mass of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone.
[0133] The post-treatment reagents are sodium oleate and sodium stearate, with a mass ratio of 1:1.
[0134] Embodiment 11
[0135] This embodiment provides a liquid phase preparation method for nano-scale ultrafine copper powder, the steps are:
[0136] S1. Prepare 2 mol / L copper carbonate alcohol solution, 10% ammonia solution, 4 mol / L ascorbic acid solution, weigh 0.2 g dispersant, and 10 g post-treatment reagent.
[0137] S2. Take 500mL of 2mol / L copper carbonate alcohol solution and place it in a water bath, control the temperature to 25°C, keep the stirring rod speed at 600r / min and stir at a constant speed, add 10% ammonia solution to adjust the pH to 9, and stir for 30min; after heating the solution to 50°C, add 250mL of 4mol / L ascorbic acid aqueous solution to the beaker, add 0.2g of dispersant, react for 30min, continue to add 1L of 4mol / L ascorbic acid solution, react again for 2h, let the solution stand at room temperature and remove the supernatant, wash it with deionized water and anhydrous ethanol 3 times in sequence, and then dry it to obtain anti-oxidation nano-scale ultrafine copper powder.
[0138] The copper carbonate alcohol solution is prepared from copper carbonate and ethanol.
[0139] The dispersant is a mixture of Tween 80, sodium dodecyl sulfate and modified pyrrolidone, with a mass ratio of 2:2:3.
[0140] The preparation method of the modified pyrrolidone comprises the following steps: mixing acrylic acid, sodium methyl allyl sulfonate, N-vinyl pyrrolidone and azobisisobutyronitrile, vacuum sealing and placing in an oil bath at 85°C for reaction for 10 hours, collecting the residue after the reaction is completed, extracting the residue with dichloromethane for 60 hours, and placing the collected reactants in a vacuum drying oven to dry to constant weight to obtain the modified pyrrolidone.
[0141] The molar ratio of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone is 2:1:3.
[0142] The added amount of azobisisobutyronitrile is 0.7% of the total mass of acrylic acid, sodium methyl allyl sulfonate and N-vinyl pyrrolidone.
[0143] Performance Testing
[0144] The specific surface area of the nano copper powder was tested by a specific surface area detector, in units of m² / g; the D10, D50, and D90 of the nano copper powder were tested by a laser particle size analyzer, and the difference between D90 and D10 was calculated. D90-D10 can represent the width of the particle size distribution. The larger the difference, the wider the particle size distribution, and the smaller the difference, the narrower the particle size distribution, in units of μm; the circularity of the nano copper powder was tested with reference to the paper "Material Particle Size and Circularity Test Based on Matlab GUI Image Processing" published by Cao Liying et al. The closer the circularity is to 1, the closer it is to the standard circular shape; the surface oxygen content of the nano copper powder was tested by a nitrogen and oxygen analyzer, in units of ppm. The results are shown in Table 1.
[0145] Table 1 Measurement results
[0146] Specific surface area D10 D50 D90 D90-D10 Roundness Surface oxygen content Example 1 2.84 0.15 0.49 0.92 0.77 1.0045 2920 Example 2 7.03 0.10 0.15 0.22 0.12 1.0007 2426 Example 3 4.35 0.18 0.28 0.42 0.24 1.0023 2779 Example 4 2.53 0.17 0.58 1.06 0.89 1.0058 4379 Example 5 6.58 0.12 0.18 0.26 0.14 1.0012 3908 Example 6 3.94 0.22 0.34 0.48 0.26 1.0029 3735 Example 7 2.19 0.53 0.82 1.17 0.64 1.0046 4298 Example 8 3.58 0.44 0.59 0.76 0.32 1.0031 4013 Example 9 2.31 0.52 0.74 0.91 0.39 1.0037 4194 Example 10 6.11 0.15 0.32 0.58 0.43 1.0032 3232 Embodiment 11 6.43 0.12 0.19 0.28 0.16 1.0013 7125
[0147] It can be seen from the embodiment 1-3 of the present invention that by adding the reducing agent again when the reduction is not completely reacted in a step, and realizing the copper powder particle size D50 distribution at different levels of 150-490nm according to the process control, and the nano copper powder has a large specific surface area, a narrow distribution, a high circularity, and a low surface oxygen content, which is not easily oxidized and can be stored for a long time. Embodiment 4-6 is a group, and it can be seen from the comparison with embodiment 1-3 that by changing the composition of the dispersant and the post-treatment reagent, the median particle size, particle size distribution, specific surface area, circularity and surface oxygen content of the nano copper powder are all affected to a certain extent, which is worse than embodiment 1-3 as a whole, but the performance of the prepared nano copper powder is still relatively excellent, and D50 is distributed at different levels of 180-580nm. Embodiment 7-9 is a group, which not only changes the composition of the dispersant and the post-treatment reagent, but also changes the pH adjusting agent and the reducing agent, and the overall relevant performance of the nano copper powder is worse than that of embodiment 4-6. The volume of the reducing agent solution added again in embodiment 10 is less, and the relevant performance is worse than that of embodiment 2. In Example 11, the nano copper powder was not post-treated, resulting in too high oxygen content on the surface of the nano copper powder, which was easily oxidized and difficult to store. Therefore, the raw materials and methods described in this application can not only control the distribution of the prepared nano copper powder D50 at different levels from 150nm to 800nm, but also optimize the particle size distribution, improve the dispersibility of the nano copper powder, reduce the particle size distribution range, and improve the circularity.
[0148] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A liquid phase preparation method for nano-scale ultrafine copper powder, characterized in that: The following steps are involved: S1. Prepare reagents and weigh drugs: prepare copper salt alcohol solution, pH adjustment aqueous solution, reducing agent solution, weigh dispersant and post-treatment reagents for standby use; wherein the copper salt alcohol solution includes copper salt and ethanol, the concentration of copper salt in the copper salt alcohol solution is 1-3 mol / L, and the copper salt is copper carbonate; the reducing agent is selected from ascorbic acid; the molar ratio of copper salt to reducing agent is 1:(1-1.2); S2, preparation of copper powder: take copper salt alcohol solution in a water bath, control the temperature to room temperature, maintain stirring at a speed of 500-700r / min, add pH adjusting aqueous solution to adjust the pH of the system to 8-10, and stir for 25-35min; heat the water bath to 50-60°C, add reducing agent solution and dispersant, stir for 25-35min, continue to add the second reducing agent solution, react again for 1-5h, let the solution stand at room temperature and remove the supernatant, wash with deionized water and anhydrous ethanol 2-3 times in turn to obtain wet copper powder, the second reducing agent solution is consistent with the reducing agent solution, the amount of the second reducing agent solution added is 3-8 times the volume of the reducing agent solution in step S2, the dispersant is selected from a mixture of sodium dodecyl sulfate, Tween 80 and modified pyrrolidone, the mass ratio of Tween 80, sodium dodecyl sulfate and modified pyrrolidone is 1: (0.8-1.2): (1-2); S3, post-treatment: add an alcohol solvent to the wet copper powder obtained in step S2 for dispersion, add a post-treatment reagent, stir at 400-600 r / min for 50-70 min at 40-50° C., let stand and remove the supernatant, wash with deionized water and anhydrous ethanol 2-3 times in sequence, and then dry to obtain nano-scale ultrafine copper powder; wherein the alcohol solvent is selected from one or more of methanol and ethanol; the post-treatment reagent is selected from a mixture of sodium stearate and sodium oleate, and the mass ratio of sodium oleate to sodium stearate is 1: (0.8-1.2); The Tween 80 has a hydroxyl value of 65-82 mg KOH / g, a saponification value of 43-55 mg KOH / g, and an HLB value of 15; The preparation method of the modified pyrrolidone comprises the following steps: mixing acrylic acid, sodium methyl allyl sulfonate, N-vinyl pyrrolidone and azobisisobutyronitrile, vacuum sealing and placing in an oil bath at 80-90°C for reaction for 6-12 hours, collecting the residue after the reaction is completed, extracting the residue with dichloromethane for 48-72 hours, and placing the collected reactants in a vacuum drying oven to dry to constant weight to obtain the modified pyrrolidone; The pH adjusting aqueous solution includes a pH adjusting agent, which is ammonia, and the mass concentration of ammonia in the pH adjusting aqueous solution is 10%; the added amount of the dispersant is 0.2%-0.6% of the mass of the copper salt; and the added amount of the post-treatment reagent is 40-60 times the mass of the dispersant.
2. A product prepared by the liquid phase preparation method of nano-scale ultrafine copper powder according to claim 1.
Citation Information
Patent Citations
Method for stably preparing nano-copper powder
CN103769598A
Spherical nanometer copper powder as well as preparation method and application thereof
CN111957986A